2013
DOI: 10.1016/j.ipm.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Inferring user knowledge level from eye movement patterns

Abstract: The acquisition of information and the search interaction process is influenced strongly by a person's use of their knowledge of the domain and the task. In this paper we show that a user's level of domain knowledge can be inferred from their interactive search behaviors without considering the content of queries or documents. A technique is presented to model a user's information acquisition process during search using only measurements of eye movement patterns. In a user study (n=40) of search in the domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…The work of Scherer et al [3], similarly to the approach followed in the present study, researched features more based on what a human could superficially hear in audios and interpret from drawings and found that the Peak Slope of the audio could discriminate between Experts and Non-Experts. Some studies suggest that it is possible to build models that can make predictions of the user's level of knowledge or expertise, based on real-time measurements of eye movement patterns during a task session [23]. In this line, distinguishing levels of expertise, based on features gathered from video while building solutions based on physics knowledge, was studied by Worsley and Blikstein [24]; their research concluded that two-handed interaction is positively correlated to expertise.…”
Section: Related Workmentioning
confidence: 99%
“…The work of Scherer et al [3], similarly to the approach followed in the present study, researched features more based on what a human could superficially hear in audios and interpret from drawings and found that the Peak Slope of the audio could discriminate between Experts and Non-Experts. Some studies suggest that it is possible to build models that can make predictions of the user's level of knowledge or expertise, based on real-time measurements of eye movement patterns during a task session [23]. In this line, distinguishing levels of expertise, based on features gathered from video while building solutions based on physics knowledge, was studied by Worsley and Blikstein [24]; their research concluded that two-handed interaction is positively correlated to expertise.…”
Section: Related Workmentioning
confidence: 99%
“…Cole et al [9] show that you can recognize existing domain knowledge of a person with this method. Further they find: "Of particular importance is the fact that eyes fixate until the meaning of the word(s) is acquired."…”
Section: Methodsmentioning
confidence: 99%
“…Further they find: "Of particular importance is the fact that eyes fixate until the meaning of the word(s) is acquired." [10]. Eye tracking can visualize the different passages of a text already known.…”
Section: Methodsmentioning
confidence: 99%
“…A recent development is to develop computational models for predicting the domain knowledge of a user. These models consider different types of interactions such as dwell time, selected document ranks, query length, reading patterns, as well as cognitive effort measured through external sensors [7,9]. While these models are useful in customizing results according to the domain knowledge of the user, they however, do not capture situations where domain experts search information in narrower sub-fields of a familiar domain.…”
Section: User Modelingmentioning
confidence: 99%